A Comparison between Different Management Surgical Approaches in the Treatment of Splenic Flexure Colon Cancer - El-Hendawy, Elsayed I.; Amin, Mohamed Farouk; Fahmy, Ahmed M.; Alattar, Ahmed Z.; Elshorbagy, Shereen; Harb, Ola A.; Gomaa, Ahmed Fathy; Embaby, Ahmed; Elsayed, Ahmed M.; Osman, Gamal; Ali, Ramadan M. (Journal of Coloproctology, 2022)
Background There are many surgical approaches which described extent of resection of the colon for adequate surgical management of splenic flexure cancer, but up till now there is no established surgical procedure, this is because the presence of double lymphatic drainage of the mesenteric vessels. Segmental resection of the colon for the management of splenic flexure cancer was a recently accepted surgical procedure.Objective In the present study, we aimed to compare three surgical management techniques to clarify the best management approach of Egyptian patients with splenic flexure cancer regarding operative, clinical, and oncological outcomes: segmental resection, and extended left or right hemicolectomy,.Materials and Methods In the present study, we included 90 patients with splenic flexure cancer. Cases were divided into 3 groups. Each group included 30 patients in order to compare three surgical techniques: segmental resection, extended left hemicolectomy, and extended right hemicolectomy.Results We have found no statistically significant differences between the three included groups regarding operative findings, postoperative complications, local recurrence, distant recurrence, disease progression, recurrence-free survival rate, progression-free survival rate, and overall survival rate. The operative time was longer, and the number of lymph nodes was higher in the extended right hemicolectomy group (p < 0.001).Conclusion We have shown that segmental resection of the splenic flexure is surgically and clinically suitable for the adequate management of operable cases of carcinoma of the splenic flexure.
Keywords: splenic flexure cancer; surgery; segmental resection; outcome